Sellar Reconstruction and Rates of Delayed Cerebrospinal Fluid Leak after Endoscopic Pituitary Surgery - Sanders-Taylor, Chris; Anaizi, Amjad; Kosty, Jennifer; Zimmer, Lee A.; Theodosopoulos, Phillip V. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objectives Delayed cerebrospinal fluid (CSF) leaks are a complication in transsphenoidal surgery, potentially causing morbidity and longer hospital stays. Sella reconstruction can limit this complication, but is it necessary in all patients?Design Retrospective review.Setting Single-surgeon team (2005–2012) addresses this trend toward graded reconstruction.Participants A total of 264 consecutive patients with pituitary adenomas underwent endoscopic transsphenoidal resections. Sellar defects sizable to accommodate a fat graft were reconstructed.Main outcomes Delayed CSF leak and autograft harvesting.Results Overall, 235 (89%) had reconstruction with autograft (abdominal fat, septal bone/cartilage) and biological glue. Delayed CSF leak was 1.9%: 1.7%, and 3.4% for reconstructed and nonreconstructed sellar defects, respectively (p = 0.44). Complications included one reoperation for leak, two developed meningitis, and autograft harvesting resulted in abdominal hematoma in 0.9% and wound infection in 0.4%.Conclusion In our patients, delayed CSF leaks likely resulted from missed intraoperative CSF leaks or postoperative changes. Universal sellar reconstruction can preemptively treat missed leaks and provide a barrier for postoperative changes. When delayed CSF leaks occurred, sellar reconstruction often allowed for conservative treatment (i.e., lumbar drain) without repeat surgery. We found universal reconstruction provides a low risk of delayed CSF leak with minimal complications.
Keywords: pituitary tumor; sella; cerebrospinal fluid rhinorrhea; neuroendoscopy; complications